The New York times index for the published news. (New York New York Times Co. [etc.], 1997)
Semimonthly with annual cumulations, 1948-57 Quarterly, Monthly with annual cumulations (1930 has also quarterly cumulations), 1913-29 1930-47.
"Master-Key to the news since 1851."
Supersedes the New York times index "Prior series" consisting of the original handwritten index for Sept. 18, 1851/Aug. 31, 1858, and the newly prepared index for Sept. 1858-Dec. 1912.
Title varies slightly.
Keywords: Newspapers -- Indexes; Indexes